IMPLIKASI PROGRAM “YES I DO” OLEH PLAN INTERNATIONAL DALAM MENGURANGI PERKAWINAN ANAK DI INDONESIA (STUDI KASUS KABUPATEN SUKABUMI) - Loudy Indah Sukma; Umi O. Retnaningsih (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Indonesia is one of the countries with the highest rates of child marriage in the world. Seeing the adverse impact of child marriage, PLAN International and its partners run the